Diagnostic accuracy of prenatal imaging for the diagnosis of congenital Zika syndrome: Systematic review and meta-analysis - Herrera, Tania T.; Cubilla-Batista, Idalina; Goodridge, Amador; Pereira, Tiago V. (Frontiers in Medicine, 2022)
OBJECTIVE: To assess the accuracy of prenatal imaging for the diagnosis of congenital Zika syndrome. DATA SOURCES: PubMed, Scopus, ISI Web of Science, and Google Scholar from inception to March 2022. Two researchers independently screened study titles and abstracts for eligibility, followed by full-text assessment. STUDY ELIGIBILITY CRITERIA: observational studies with pregnant women with Zika virus infection were included. The index tests included ultrasound and/or magnetic resonance imaging. The reference standard : 1) perinatal death, stillbirth and neonatal death within the first 48h of birth, 2) neonatal intensive care unit admission, and 3) composite adverse perinatal outcomes. Case reports were excluded with fewer than five cases. A data extraction form was used. SYNTHESIS METHODS: We extracted 2 x 2 contingency tables.Pooled sensitivity and specificity were estimated using the random-effects bivariate model. Risk of bias was assessed using quality assessment for diagnostic accuracy studies version 2-tool. The certainty of the evidence was evaluated with grading of recommendations. RESULTS: 1,696 citations were identified from the databases. After removing duplicates (635), 1,149 records were screened, of which 91 were eligible for full text review.Of these studies, 73 were excluded , leaving 18 studies for final inclusion in the qualitative analysis. There was a significant variation in the studies included with regard to the prenatal image assessment and the outcomes evaluated. Six studies with 763 pregnant women were included in the meta-analysis. Across studies based on the random-effects model, the ultrasound sensitivity ranged from 12 to 100%, whereas the specificity ranged from 50 to 100%. The positive likelihood ratio was 24.9 (95% CI: 2.11 to 293.2), and the negative likelihood ratio was 0.19 (95% CI: 0.02 to 2.05).. The area under the hierarchical summary receiver operating characteristic curve was 0.97 (95% CI, 0.72 to 1.00) and the summary diagnostic odds ratio was 140 (95% CI, 3.0 to 7564, P < 0.001). CONCLUSION: the accuracy of prenatal image for diagnosis of congenital Zika syndrome remains low at this time. The certainty of the available evidence is low. Future studies should evaluate the creation of standardized algorithms that could differentiate the different spectrum of the disease.